Role of intrinsic motivation and government policies in adoption of sustainable agriculture practices by farmers in Maharashtra, India - Deepika Swami; Devanathan Parthasarathy (Farming System, 2024)
Indian agriculture system is facing severe crisis due to multiple stressors, including climate change, excessive use of fertilizers and pesticides, poor socio-economic condition of farmers and water scarcity. Adoption of sustainable form of agriculture is one of the remedies to deal with these stressors. Despite this, adoption of Sustainable Agriculture Practices (SAPs) is quite limited among farmers, which necessitates understanding the factors driving farmers’ adoption of SAPs. So far, studies have majorly prioritized socio-economic and demographic variables and lack comprehensive understanding of institutional and behavioural factors towards adoption of SAPs by farming community. Current research aims to address the underlying gaps, by focusing on understanding the contribution of institutional, attitudinal and perceptual factors manifesting in attitude and perception. Thereby, to understand the factors driving adoption of SAPs, we conducted a field survey of 400 farmers across Vidarbha and Marathwada regions of Maharashtra, India. We further used structural equation modeling to model the relationship between SAPs and its driving factors i.e., intrinsic motivation and institutional factors. Findings show that perceived usefulness, easiness and compatibility are strong motivation in implementing sustainable agriculture practices by farmers. These factors need to be inculcated among farmers for improving their adoption of SAPs. The subsidy provided on seeds, fertilizers, and water leads to overutilization of these resources, which itself is an unsustainable practice. Only incentives and extension services showed a statistically significant and positive relationship with the adoption of SAPs. Findings can help policymakers in designing targeted interventions for farmers and agriculture sector in India.